The Relationship between Maternal Haemoglobin and Haematocrit with Low Birth Weight and Preterm Labour - Behnaz Sovizi; Hamid Kermani Mokhar; Mitra Eftekhari Yazdi (Mashhad University of Medical Sciences, 2019)
Background & aim: Low levels of maternal haemoglobin and haematocrit in the first, second, and third trimesters are considered as possible risk factors regarding low birth weight (LBW) and preterm labour (PTL). The present study aimed to evaluate the relationship between maternal haemoglobin (Hb) and haematocrit (HCT) levels with LBW and PTL. Methods: This cross-sectional study was conducted on 383 pregnant women who were admitted in postnatal ward and gave birth to live neonates. Maternal Hb and HCT levels in the first, second, and third trimesters were obtained from medical records. The data were analysed using chi-square test by SPSS software (version 19). Results: A total of 383 pregnant women with the mean age of 25.5 years were participated in this study. There was a significant relationship between maternal HCT in the first, second, and third trimesters with LBW (P